Rooms that judge: domestic space, moral surveillance, and selfhood in Uzbek and English literary discourse - Anvarjonova, Zarifaxon Abrorjon qizi (The Lingua Spectrum, 2026)
This article examines domestic space as a conceptual-metaphorical structure of moral surveillance and selfhood formation in Uzbek and English literary discourse. Drawing on Conceptual Metaphor Theory and spatial literary criticism, it compares Abdulla Qahhor’s “Dahshat,” O‘tkir Hoshimov’s Ikki eshik orasi, Jean Rhys’s Wide Sargasso Sea, and Kazuo Ishiguro’s The Remains of the Day. The study argues that houses, rooms, compounds, thresholds, attics, halls, windows, and walls function not only as narrative settings but also as cognitive and ideological structures through which social power becomes visible and internalized. The governing metaphor, THE HOUSE IS A MORAL AUTHORITY, is analyzed in relation to patriarchal custom, Soviet ideological surveillance, colonial authority, racial hierarchy, and English class discipline. The comparative reading shows that domestic space may judge, discipline, restrict, or absorb selfhood while preserving culturally specific forms of resistance, memory, and moral witness. It also demonstrates how metaphor organizes plot, character, and ethical conflict.